Prevalensi dan Faktor Risiko Anemia pada Pekerja Perempuan di Rumah Sakit : Literature Review Study - Sesmeri Haryani; Delmi Sulastri (Jurnal Ners, 2025)
Anemia, particularly iron deficiency anemia (IDA), is a major global health issue among women of reproductive age, including female hospital workers such as nurses, midwives, and other healthcare personnel. This study aims to review the literature on the prevalence and risk factors of anemia among female hospital workers. A systematic review design with a descriptive narrative synthesis approach was employed, following the PRISMA guidelines. Literature was retrieved from PubMed, Scopus, and Google Scholar using relevant keyword combinations. Out of 10,203 articles identified, six studies met the inclusion criteria. Findings revealed a high prevalence of anemia among female workers, especially those under 40 years of age, experiencing heavy menstruation, having poor dietary habits, and working night shifts. Anemia's impact includes fatigue, reduced productivity, and increased risk of work-related errors. Therefore, a comprehensive intervention strategy involving regular screening, nutritional education, and gender-responsive workplace policies is essential to improve women's occupational health in the healthcare sector.